Relaciones interprofesionales, ¿problemas éticos o problemas técnicos? - Maestro, Irache; Sanz, Jaime (Psicooncología, 2004)
The purpose of our article is to communicate the need of taking into account ethic values in the decision making process. The reason for this need is the lack of communication among the professionals of different medicine fields. We show a 84 year-old patient with many comorbidities, to whom a Neurophysiological Study was performed in order to confirm an irrelevant diagnosis in his overall process. This study did not suppose any therapeutic change and, therefore was useless. Taking into account the happenings and values of the described situation, we show the ethic dilemma the professional has to think about. This reveals the imbalance between both aspects of nowaday’s medicine: the scientific and technique (episteme) and the humanistic (doxa). The right junction between both aspects is needed to reach medicine´s main goal which is to defend the patient’s interest.